Inter-state propagation of black chicken for empowerment of rural women in Jammu and Kashmir - Azad, Mandeep Singh; Bhadauria, Pragya; Lal, Banarasi; Keshava, Keshava; Singh, Rajbir (Indian Farming, 2022)
In the last decade, poultry sector has come up in a big way in some of the districts of Jammu and Kashmir like Jammu, Kathua, Udhampur, Pulwama, Srinagar and Budgam. It is gaining impetus in the state as there is a handsome collection of profit due to quick returns in this business, availability of maize, plenty of manpower and a huge market for consumption of poultry and poultry products. Many educated unemployed youths are taking poultry farming as a sustainable means of earning their livelihood. The state has enormous potential and conducive environment for poultry development on commercial lines, still, the it is deficit in egg by 46% and poultry meat by 31% despite 84% of the population being non-vegetarian. Per capita consumption of egg is 100 and poultry meat is 1.2 kg per person per annum in urban areas but in rural areas, it is only 15 eggs and 0.15 kg of poultry meat. The GoJK intends to tap the possibilities of rural poultry production to promote and support rural masses for livelihood security, entrepreneurship development and nutritional security. Despite the strenuous efforts, poultry farming is not picking up pace in these areas and small poultry farmers are in great loss from the big market players who have taken over the whole market of Jammu and Kashmir. These big companies in the market have made it tough for local poor poultry producers to compete in terms of rates and quality. The only way out is to make the rural backyard poultry an economic venture rather than merely a subsistence tool so that farmers can get a good market return on investment and it can also contribute to nutritional security.